Bektashi Baba Dr. Hasan Ragıp Erensel: One of Atatürk’s Doctors - Özata, Metin (Journal of Alevism-Bektashism Studies, 2024)
Gazi Mustafa Kemal Atatürk, a charismatic leader and intellectual, had many physicians whom he befriended, assigned tasks to, and received treatment from, from his early days as a young officer until his death. One of these physicians was Dr. Hasan Ragıp Erensel, whom he met during the Battle of Gallipoli.Dr. Erensel was born in 1881 in the town of Nevrekop near Thessaloniki. He graduated from the Medical School (Mekteb-i Tıbbiye) in 1905 as a medical captain and began his service in the army. In 1912, he went to Germany for a course and returned to Istanbul a year later. On January 6, 1915, he was appointed as the assistant chief physician of the Gallipoli Group.During the Gallipoli War, his wife, Anna Schwartz, an Austrian nurse, was martyred in a bombing. Anna Schwartz’s grave is in the Eceabat Yalova village cemetery, and the local people also refer to it as “Ana Hatun’s Grave,” reminiscent of her real name “Anna.” On May 3, 1916, Dr. Erensel was appointed as the chief physician of the 17th Corps, and he retired from the military as a lieutenant colonel on June 30, 1927. Dr. Hasan Ragıp Erensel, who participated in the Italo-Turkish War, the Balkan Wars, World War I, and the War of Independence, was awarded the War Medal, the German Iron Cross 2nd Class, the Austrian Franz Joseph Medal, and the Independence Medal for his achievements.Dr. Erensel, who served as a physician at the Çankaya Mansion, established a close relationship with Atatürk and personally attended to Atatürk’s health problems. This indicates the connection between Atatürk and Bektashism. Dr. Erensel, who was a physician at the Çankaya Mansion during Atatürk’s time, was a Bektashi Baba. He also guided Ali Naci Baykal Dedebaba for many years and had a spiritual influence on Dr. Bedri Noyan. Dr. Erensel passed away in Ankara on January 26, 1953.
Keywords: Atatürk; Dr. Hasan Ragıp Erensel; Nurse Anna Schwartz; Bektashi Baba